An Introduction to African and Afro-Diasporic Peoples and Influences in British Literature and Culture before the Industrial Revolution - Elmore, Jonathan; Halpin, Jenni (Open textbook library., 2021)
Funded by the University System of Georgia’s “Affordable Learning Georgia” initiative, An Introduction to African and Afro-Diasporic Peoples and Influences in British Literature and Culture before the Industrial Revolution corrects, expands, and celebrates the presence of the African Diaspora in the study of British Literature, undoing some of the anti-Black history of British studies.